LINGUISTIC AND PRAGMATIC PERSPECTIVES OF IMPERATIVE SENTENCES - Abdusalomov F. A. (Bright Mind Publishing, 2025)
This paper explores the linguistic characteristics and pragmatic functions of imperative sentences, with a focus on their usage in different languages, particularly in military discourse. Imperative sentences are considered to be the most direct means of communication, used to give orders, instructions, or requests. The structure, meaning, and communicative function of imperative sentences are discussed with reference to their morphological properties, syntactic features, and pragmatic roles. Examples from English, Uzbek, and other languages are used to illustrate the diversity and universality of this sentence type in everyday communication and specialized discourse such as military commands. The article emphasizes the impact of imperative sentences on decision-making, coordination, and effective communication in military operations and examines the cultural nuances that influence their usage.
Keywords: Imperative sentences, linguistic analysis, pragmatic functions, military discourse, communication.